Transaction Costs and Evolution of New Institutions in Farmers’ Managed Irrigation System in Nepal - Bhattarai, Ram Chandra; Bhusal, Tara Prasad (Economic Journal of Development Issues, 2017)
The paper examines the impact of transaction costs on institutional development and agricultural productivity in Nepal and analyzes the factors influencing transaction costs. A field survey of in the Kathmandu and Palpa districts of Nepal, reveals that transaction costs amount to 3 %of the net farm return and 3.3 % of the total cost of production. It is rational for farmers to invest in ensuring reliable irrigation and better institutional management because farmers with reliable irrigation and better institution reported higher productivity.Economic Journal of Development IssuesVol. 19 & 20 No. 1-2 (2015) Combined Issue, page: 1-21